2016
DOI: 10.1155/2016/6075679
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nigella sativa and Its Active Constituents in Learning and Memory

Abstract: The loss of the ability for learning and memory is a prominent feature of dementia, which affects millions of individuals all over the world, due to either neurodegenerative diseases or brain injury. Although a lot of information is known about the pathology involved, treatment remains elusive at best. The Black Seed of Nigella sativa has been historically and religiously used for thousands of years for preventing and treating many different kinds of diseases. This review article looks at Nigella sativa and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
70
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 33 publications
1
70
0
2
Order By: Relevance
“…The downregulation of the protein levels of cyclooxygenase‐2 (COX‐2) and tumor necrosis factor‐α (TNF‐α) in the brain due to TQ treatment may be accepted as an indication of anti‐inflammatory effect of this molecule . The effect of TQ on the hippocampus gained more attention on the basis of its enhancing activity on the learning and memory according to studies related amelioration of cognitive decline by preventing oxidative stress in diabetes and restoring oxidative balance and cholinesterase activity in Aβ accumulation to exhibit its neuroprotective effects …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The downregulation of the protein levels of cyclooxygenase‐2 (COX‐2) and tumor necrosis factor‐α (TNF‐α) in the brain due to TQ treatment may be accepted as an indication of anti‐inflammatory effect of this molecule . The effect of TQ on the hippocampus gained more attention on the basis of its enhancing activity on the learning and memory according to studies related amelioration of cognitive decline by preventing oxidative stress in diabetes and restoring oxidative balance and cholinesterase activity in Aβ accumulation to exhibit its neuroprotective effects …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the bioavailability of TQ in blood was previously calculated as ≈58% with a lag time of ≈23 min when it was administered by intragastric intubation at a dose of 20 mg kg −1 . In addition, TQ has been reported to possess potent lipophilicity and, thus, it can cross the blood brain barrier . In case of exogenous administration under normal conditions, there is limited information about the effect of TQ.…”
Section: Introductionmentioning
confidence: 99%
“…This study uses the extract of ethanol NS in which contained various types of bioactive (multiple compounds). Bioactive suspected estrogenic, neuroprotective, antioxidant effects and antiinflamatory effects are thymoquinone, -terpinen, p-cymen, carvacrol, thymol, flavonoids and unsaturated fatty acids in the form of linoleic acid (Sahak et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…In ancient texts and historical documents, NS has been mentioned as a notable healer for a range of ailments (Randhawa, 2008&Sahak, 2016 traditional practice of its usage in the muslim primarily due to the authentic prophetic statement that NS is a cure for all, except death; that was quoted by a renowned Muslim scholar, Al (1976). The efficacy ofthe NS oil is mostly attributed to its quinone constituents in the NS fixed and essential oil, which is especially endowed with thymoquinone (TQ), a significant bioactive constituent making up 30 of the total compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Scientific studies have shown it to possess amongst , antispasmodic (Ahmad et al, 2013). NS has a long history of folklore usage in different recognized as a 'miracle cure' for its ability to treat various diseases and assist s own natural healing process (Goreja, historical documents, NS healer for a range Sahak, 2016 Sahak, 2016;Khan, 1999) The decline in or loss of the ability for learning and memory is a prominent feature of dementia, which affects millions of individuals all over the world. Alzheimer's disease (AD) is one of the most common subtypes of dementia (Fratiglioni, 1999) neurodegenerative disease characteri deposition of amyloid plaques, neurofibrillary tangles, cerebral oxidative stress, inflammation, and atrophy, and impaired neuronal function (Bamberger & Landreth, 2002;Di Patreet al, 1999,&Nicolakakiset al,2006.…”
Section: Introductionmentioning
confidence: 99%